How powerful are the multinational corporations? - Ehrenfried Pausenberger (Intereconomics, 1983)
Much unease, distrust and criticism is being expressed in the current debate about the potential power of multinational corporations and the possibilities of abuse. What is the basis for the power of the multinationals, and what possibilities are available for controlling and limiting that power?
Keywords: 330; Multinationals